PRAKTIK PENGHINDARAN PAJAK DAN MANAJEMEN LABA SEBELUM DAN SAAT PANDEMI COVID-19 - Hudzaifah Nur Azzahro; Sartika Wulandari (Jurnal Bina Akuntansi, 2023)
The Covid-19 Pandemic has caused Indonesian’s Economy weak. The Government seeks to restore the national economy with various facilities, such as tax incentives. This conditions will affect the practice of tax avoidance and earnings management. This study aims to determine the differences in tax avoidance and earnings management practice before and after Covid-19 pandemic. This study used quantitative data sourced from the company’s annual financial statements. The population used is healthcare companies listed on the Indonesia Stock Exchange (IDX) in the 2019-2020. The sample was determined by purposive sampling technique using several criteria and then resulted in 30 samples from 15 healthcare companies. The method used in this study is wilcoxon non-parametic test using Eviews 12. The results of this study conclude that there is no difference in tax avoidance practices before and during the Covid-19 pandemic. Meanwhile, the level of earnings management behavior during the Covid-19 pandemic was lower than the earnings management before the Covid-19 pandemic.